2016
DOI: 10.1111/sum.12314
|View full text |Cite
|
Sign up to set email alerts
|

Mulch effect on successive crop yields and soil carbon in Tonga

Abstract: Intensification of crop production in Tonga has resulted in a move to mechanical soil preparation, often with a rotary hoe, and a consequent loss in both chemical physical fertility. An experiment was conducted on a clay loam soil (Typic Argiudoll) on the Forestry Vaini Research Station, Tongatapu Island, Tonga, to investigate the effect of a once-off application of mulch on yield and quality of watermelon, maize and capsicum grown in rotation over a 1-yr period. The treatments applied were a nonmulched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…• le mulch a certainement protégé la macrofaune du sol qui a pu subsister dans les couches superficielles du sol après la défriche. Cette macrofaune, majoritairement composée de lombrics (adultes, oeufs) et de fourmis, occasionnellement de termites, a certainement bénéficié de la protection du mulch, connu pour maintenir fraîcheur et humidité (Manu et al, 2017) ; dans ces conditions, la macrofaune a pu reprendre plus rapidement et régénérer en partie la macroporosité perdue (Lal, 1988).…”
Section: éPaisseur Impactée Par La Compaction Juste Après La Défricheunclassified
“…• le mulch a certainement protégé la macrofaune du sol qui a pu subsister dans les couches superficielles du sol après la défriche. Cette macrofaune, majoritairement composée de lombrics (adultes, oeufs) et de fourmis, occasionnellement de termites, a certainement bénéficié de la protection du mulch, connu pour maintenir fraîcheur et humidité (Manu et al, 2017) ; dans ces conditions, la macrofaune a pu reprendre plus rapidement et régénérer en partie la macroporosité perdue (Lal, 1988).…”
Section: éPaisseur Impactée Par La Compaction Juste Après La Défricheunclassified
“…With the incorporation of mulch to the soil for establishment of grasses it is possible to obtain significantly higher results in relation to treatments without the addition of straw, having a greater amount of vegetation of grasses and biomass [44]; also, improves soil moisture retention by reducing evaporation [43]. Equally, addition of vegetative mulches to have a positive impact on the yield and profitability of the plants, which could largely be attributed to the mulches modifying soil temperature and moisture and in controlling weeds [50]; moreover, the cover crops and living mulches bring many benefits to crop production and plants, such as soil erosion control, reduce weed pressure, increase soil organic matter content, improved soil structure and water infiltration, decreased water runoff, reduced surface soil temperature and water evaporation [51]. The yields obtained were mainly benefited by the high rainfall recorded in the area, which was 346.0 mm, about 96 mm above the annual average in the area ( Figure 1B) [47].…”
Section: Percentage Of Establishment and Yield Of Dry Mattermentioning
confidence: 99%
“…Figure 6. Compilation of study from various literatures (Ferre 2014, Villarino 2017, Chan 2008, Manu et al 2017. This compilation suggests that soil moisture in lower soil organic carbon can be improved by intensification of mulching to improve plant growth and crop yield.…”
Section: Intensification Of Mulching To Improve Soil Moisture and Cromentioning
confidence: 99%
“…By addition of organic material for mulches, light from the sun can be intercepted and temperature can be maintained in a relatively acceptable level. Manu et al (2017) have examined the effect of various vegetative mulching materials on various crops. They concluded that improvement of yield shown by those crops attributed by lowering soil temperature and increasing soil moisture.…”
Section: Introductionmentioning
confidence: 99%